Livelihood Strategy Masyarakat Pasca Banjir di Desa Bincau Muara Kecamatan Kabupaten Banjar - Werdana, Aulia Rahman; Damaiyanti, Varinia Pura (Prodi Sosiologi FISIP ULM, 2024)
Bincau Muara Village, Banjar Regency, is one of the villages most severely affected by flooding in late 2020 to early 2021. This research aims to find out how the community's livelihood strategy in maintaining its sustainability after the flood in Bincau Muara Village. This research uses a qualitative approach. The informants consisted of ten people who were obtained using the snowball technique. The results showed social action (value and instrumental rationality) from the community, namely preparing at least one canoe per house for flood preparedness and taking directed steps from Village officials who must take into account the situation before the flood occurs. Then the livelihood strategy is carried out through a pentagonal asset approach, namely: 1) human capital through increased ability in economic activities that are adaptive to flooding; 2) natural capital through the utilisation of situations and conditions when flooding is occurring; 3) financial capital through strategies to fulfil economic needs after flooding that occurs for the long term; 4) social capital through optimising the function of GAPOKTAN (Gabungan Kelompok Tani) to facilitate farmer groups in terms of assistance for the continuity of their work; and, 5) physical capital through the provision of basic infrastructure and facilities in Bincau Muara Village to support the community's livelihood process. Furthermore, Gemmeinschft and Gesselschft as a support for social conditions among various social factors and livelihood strategies carried out collectively.